Exploring the Essential Stroke Care Structures in Tertiary Healthcare Facilities in Rivers State, Nigeria - Osborne Ikechuckwu Osuegbu BSc, MSc; Foluke Olukemi Adeniji MBBS, MSc; Golden Chukwuemeka Owhonda MBBS, FWACP; Rogers Bariture Kanee BSc, MSc; Eric Osamudiamwen Aigbogun BSc, MSc, PhD (SAGE Publishing, 2022)
This study evaluated the essential stroke care structure available in the two Tertiary Health Facilities in Rives State, Nigeria. This was a descriptive survey involving the Stroke Care Survey and Assessment Tool (checklist/questionnaire) developed by the World Stroke Organisation to obtain information about the available essential stroke care structure (facilities, equipment, personnel and management protocol) at the two tertiary health facilities (RSUTH & UPTH). The study gathered relevant information, which was summarised into tables and graphs using Microsoft Excel 2016. From the results, although facilities had A and E departments, dedicated stroke units (fixed or mobile) were unavailable, and there was no locally developed protocol to support rapid triage of stroke patients. The facilities and equipment were either unavailable or insufficient. Only one health facility (RSUTH) provided 24 hrs/7 days laboratory services. The workforces were a mix between regular clinical staff and some specialists. Tissue plasminogen activator (tPA) use was non-existent, though specialists were trained on its administration. There was no locally developed or adopted stroke-specific clinical guidelines. In conclusion, the structural services available for stroke care within the studied tertiary health facilities were poor, unavailable or grossly insufficient. The state facility (RSUTH) suffered the most in terms of unavailable national support and staff development.